THE ROLE OF WOMEN FARMER GROUPS IN HOUSEHOLD INCOME IN KEDIRI - Erlin Widya Fatmawati; Ferica Agustin; Muhammad Bagus Yulianto (Faculty of Animal and Agricultural Science, Diponegoro University, 2022)
The role of women in the household is very important today in the welfare of the family and also the development in society. It is necessary to provide assistance in providing useful activities for women through women farmer groups, so that women are not only seen as a burden on family life but also can contribute to their families and surrounding communities. The purpose of this study was to determine the activities of the women farmer group in Kediri Regency and to determine the role of the women farmer's Group in Kediri Regency. This research was conducted in Kandat Village, Kediri Regency by taking 30 respondents from the women farmers group. Data analysis carried out in this study came from data from interviews, field notes and documentation. Data analysis was done by organizing data into units, synthesizing, compiling into patterns, choosing what is important and what will be studied, and drawing conclusions that are easily accessible. Results of this research regarding the role of members of the women farmer groupin Kandat Village were quite varied, where most of them are housewives who take care of family, mothers who work outside, or have a business at home. Their role had changed slightly from those who were initially housewives, now earn additional income. This activity should be fostered in a sustainable manner so that the members of the women farmer grouphave activities that have a positive impact on the household and also the community.